Patterns of Middle-Class Communities Adaptation to the Village SDGS Program in Bogor Regency - Nur Meily Isnaeni; Moh Dulkiah; Asep Dadan Wildan (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2022)
Village is the smallest territorial space in Indonesia with a complex socio-economic problem. For this reason, the village SDGs was born as a micro-based global development agenda expected to realize village development efficiently. This program has the main objective of “No One Left Behind” with 18 main objectives that cover all levels of society. Among the best ideas in the 18 goals, the conclusion is still focused on sustainable village development through eradicating lower-class social issues with upper-class support. Then the question arises,